Effect of Patent Expiry on the Performance of Innovator Multinational Pharmaceutical Companies in a Low Middle Income Country - Khalil, Farrukh; Onyango, Joseph Odhiambo (Frontiers in Medical Technology, 2022)
Patent expiry or Loss of exclusivity (LOE) exposes innovator pharmaceutical companies to changes in the market dynamics brought about by increased production of generics by rival companies. The innovators of Pharmaceutical Multinational Companies in emerging markets are facing a significant challenge with their soon-to-expire blockbusters' patents. The methodology involved a descriptive survey design and utilized both qualitative and quantitative designs for data collection, analysis, and presentation. The study found a direct relationship between patent expiry and generic production, which affects the performance of innovator pharmaceutical companies. Generics production increasingly occurs with patent expiration having a strong positive direct correlation after patent expiration and subsequent performance. There is a significant effect of patent expiry on generic production and a subsequent decline in the performance of multinational innovator companies in the pharmaceutical industry. The competitive pressures created by generics due to fair prices necessitate customers to opt for cheaper drugs. This study recommends that innovator companies come up with strategies to tap into the Kenyan market by leveraging generic production through collaborative manufacturing with generic companies to share revenues.